Adsorption and Reactive Desorption on Metal–Organic Frameworks: A Direct Strategy for Lactic Acid Recovery. Issue 3 (29th November 2016) - Stassin, Timothée; Reinsch, Helge; Van de Voorde, Ben; Wuttke, Stefan; Medina, Dana D.; Stock, Norbert; Bein, Thomas; Ameloot, Rob; De Vos, Dirk
Abstract: Biomass‐derived lactic acid (LA) is an important platform chemical towards the sustainable production of numerous materials. However, the fermentation process currently in use is limited by the difficult recovery of the LA product from the fermentation broth and results in the generation of stoichiometric amounts of gypsum waste. Herein, we show that metal–organic frameworks (MOFs) of the UiO‐66(Zr) type are effective adsorbents for the separation of LA from aqueous (buffer) solutions. These frameworks based on zirconium clusters and terephthalic acid derivatives display a tremendous uptake (up to 42 wt %) and a high affinity for LA. The latter can further be tuned by changing the hydrogen‐bonding properties of the functional groups present on the organic ligand. A Rietveld refinement disclosed the specific interaction of LA with the clusters of UiO‐66(Zr) and a preferential adsorption on open zirconium sites. Taking advantage of the catalytic activity of UiO‐66(Zr), desorption of LA was performed in alcohols to recover up to 73 % as ester. Applied to the recovery of LA, adsorption and reactive desorption offer a direct and gypsum‐free strategy as an alternative for the current multi‐step process. Abstract : MOFs to the rescue : The current fermentative production of biomass‐derived lactic acid requires a tedious, non‐sustainable, multi‐step separation process. The adsorption and desorption of lactic acid on high‐affinity porous crystalline metal–organic frameworks opens a direct and gypsum‐waste‐free alternative recovery route.